Teaching and Learning of Pali as Traditional System of Phrapariyatidhamma in Thailand - Pansa, Boonmee (International Journal of Multidisciplinary in Management and Tourism, 2020)
The following chapter presents the situation and role of the Pāli language in Thailand. Most Buddhists, who believe in Buddhism in Thailand, use Pāli, the language in which the Buddha had preached to pray. Monks and novices always use Pāli for preaching the teaching of the Buddha to the Thai people. Furthermore, in Thailand Pāli is being taught to Buddhist monks as well as to common people from the level of the primary school to the university. But the curriculum of the Pāli studies for the Buddhist monks is different from that of the common people. For the Buddhist monks, the Pali studies are divided into two systems; one system is approved by the Ministry of Education but conducted by the Sangha. This system has a curriculum of education similar to that of the current educational system of the Thai people. The other system which is organized by the Sangha is only for the Buddhist monks. But at here has been discussed only system which is organized by the Sangha which is called the Traditional system of Phrapariyatidhamma.